Analisis QoS (Quality Of Service) Pada Jaringan Rt/Rw Net Untuk Peningkatan Efisiensi Dan Produktivitas Layanan - Muhammad Jordan; Khairul Warisin Hammami; Firmansyah Firmansyah (Universitas Islam Al-Azhar Mataram, 2024)
In an increasingly advanced digital era, computer networks play an important role in supporting various activities, including in the community-initiated RT/RW Net environment. This research aims to analyze Quality of Service (QoS) on the RT/RW Net network to improve service efficiency and productivity. The research method used is the experimental method, which involves data collection through the Mikhmon application to monitor network performance. QoS measurements were made based on four main parameters: throughput, delay, jitter, and packet loss.The results show that the RT/RW Net network has excellent throughput with a value of 1471 Kb/s, average delay of 3.623 ms, jitter of 3.63 ms, and packet loss of 0%, all of which fall into the